GLASS PRODUCTION OF THE TASHKENT OASIS (SHASH-ILAK) IN THE 9TH-12TH CENTURIES - Normurodov D. R. (TARIXIY TADQIQOTLAR, 2025)
The article covers the glassmaking of the 9th-12th centuries in the Tashkent oasis, which in ancient times and the Middle Ages was a historical and cultural region of Chach, Shash-Ilak. It describes the study of glass items found during archaeological research conducted in the oasis sites from the late 19th century to the present, such as Binkat-Tashkent, Bonokat-Shahruhiya, Kanka-Kharashkat, Kabarna-Kavardan, Tunkat-Imlok, Abrlig-Oblik, their preparation methods, types of flowers, and their functions. It is noted that high-quality glass products were produced in Shash-Ilak, the production of which was connected with the aesthetic taste and culture of the population.